Exploring the meaning in parametricism: a semiotic approach - Hardi K. Abdullah (Journal of Asian Architecture and Building Engineering)
Parametricism appeals and promises a communicative meaning that is distinguished from Modernism in the way that the encoding process starts with the articulation of the formal composition and structural morphology. This study draws on interpretative semiotics to address how Parametricism communicates its users and context. An analytical semiotic framework is developed from the literature review of semiotics and the parametric design paradigm. The present study identifies three interaction dimensions (building – user, building – context, and building – architect) that Parametricism establishes to communicate with its users and environment. These dimensions are described and analysed using Eco’s semiotics conviction of denotation and connotation dimensions. Designed by Zaha Hadid Architects (ZHA), the Heydar Aliyev Cultural Centre in Baku is chosen as a case study. It concludes that Parametricism encompasses not only the organisation level, but also includes phenomenological articulation and semiological signification. Parametricism communicates with its context as a “field” rather than an “object”, thus blurring the rigid line between architecture and urban, inside and outside, ground and volume, cladding and flooring.